Thermochemical technologies for conversion of biomass and waste into light olefins (C2-C4) - Hualun Zhu; Mohammed Babkoor; Marc-Olivier Coppens; Massimiliano Materazzi (Fuel Processing Technology)
The demand for light olefins, including ethylene, propylene, and butene, continues to grow as they serve as essential intermediates for numerous chemical products. Traditional production methods rely heavily on fossil resources, raising concerns about environmental impact and resource depletion. As the global focus shifts towards sustainability and carbon neutrality, researchers are exploring alternative and renewable feedstocks, such as biomass and waste, to produce light olefins. This review paper provides an in-depth analysis of the recent advancements and strategies employed in the production of light olefins directly and indirectly from biomass and waste via thermochemical processes. Emphasis is placed on the role of catalysis in these approaches, covering catalyst types, applications, and performance. Furthermore, this review explores process intensification approaches as potential avenues for enhancing the efficiency and sustainability of olefin production. By presenting a holistic view of the current state of olefin production from recovered feedstocks, this work aims to contribute to the development of greener and more sustainable bio-based industries, ultimately fostering a transition towards a circular economy and mitigating the environmental impact of the petrochemical industry.